Clinical presentation, diagnostic findings and outcome in dogs diagnosed withpresumptive spinal‐only meningoen‐cephalomyelitis of unknown origin. (March 2017) - Cornelis, I.; Volk, H. A.; Van Ham, L.; De Decker, S.
Abstract : Objectives: To summarise clinical presentation, diagnostic findings and long‐term outcome for dogs clinically diagnosed with meningoencephalomyelitis of unknown origin affecting the spinal cord alone. Methods: Medical records were reviewed for dogs diagnosed with presumptive spinal‐only meningoencephalomyelitis of unknown origin between 2006 and 2015. Results: 21 dogs were included; the majority presented with an acute (43%) or chronic (52%) onset of neurological signs. Ambulatory paresis was the most common neurological presentation (67%). Neurological examination most commonly revealed a T3‐L3 myelopathy, and spinal hyperaesthesia was a common finding (71%). A spinal cord lesion was visible in 90% of cases on magnetic resonance imaging. Eighteen lesions (86%) showed parenchymal contrast enhancement and 17 lesions (81%) showed contrast enhancement of overlying meninges. All dogs were treated with immunosuppressive doses of glucocorticosteroids, sometimes combined with cytosine arabinoside. At time of data capture, 10/21 dogs (48%) had died or been euthanased because of the condition. Overall median survival time was 669 days. Clinical Significance: Meningoencephalomyelitis of unknown origin should be considered in the differential diagnosis of dogs presenting with a progressive myelopathy. Magnetic resonance imaging features can possibly help to distinguish presumptive meningoencephalomyelitis of unknown origin from other more common spinal diseases. Overall, long‐term survival is guarded, approximately 50% of dogs will die or be euthanased despite appropriate therapy.